206PPopulation-based validation of the risk stratification among prostate cancer patients. (24th November 2019) - Xie, M
Abstract: Background: To compare discriminant ability of risk stratifications for prostate cancer in three authoritative guidelines: National Comprehensive Cancer Network clinical practice guideline (NCCN-g), American Urological Association / American Society for Therapeutic Radiology and Oncology/ Society of Urologic Oncology Guideline(AUA-g) and European Association of Urology- European association of nuclear medicine- European Society for Radiotherapy and Oncology- European Society of Urogenital Radiology- International Society of Geriatric Oncology guideline(EAU-g). Methods: 511916 patients with one primary prostate cancer diagnosed between 2004 and 2016 were identified using the Surveillance, Epidemiology, and End Results (SEER, submitted in) database of the National Cancer Institute. Patients were excluded from analysis if < 18 years of age, not adenocarcinoma, diagnosed at autopsy or death certificate only, with an unknown follow-up, incomplete clinical and demographic information, leaving 287333 patients in this cohort. Patients were categorized as different risk stratifications by three latest guidelines (NCCN-g, AUA-g and EAU-g) respectively. Follow-up endpoint was prostate cancer specific mortality (PCSM), cutoff date was December 31, 2016. Kaplan–Meier analysis, multivariable Cox regression and area under the receiver operating characteristics (ROC) curve (AUC) analyses were performed. Results: The 287333 patients are all from 2004 to 2015. Median follow-up was 69 months (IQR: 39-104). For the three risk stratification modalities, all 6 risk groups in NCCN-g, 5 risk groups in AUA-g and 5 risk groups in EAU-g independently predicted PCSM. NCCN-g yielded 3.1-fold HR differences between low risk group and intermediate risk group, 14.8-fold HR differences between low risk group and high risk group, 33.0-fold HR differences between low risk group and very high risk group, 56.2-fold HR differences between low risk group and regional group, and 148.9-fold HR differences between low risk group and metastatic group. AUC is 0.8332, 0.8309 and 0.7868 in NCCN-g, AUA-g and EAU-g. Conclusions: This large population-based analysis confirms the better discriminant properties of the risk stratification method in NCCN guideline. Legal entity responsible for the study: Peking University First Hospital radiation oncology department. Funding: Has not received any funding. Disclosure: The author has declared no conflicts of interest.